Organic Base-Mediated Carboxylation of (Hetero)aromatic Compounds Using Supercritical Carbon Dioxide (scCO2) - Chetty, Lloyd C.; Kruger, Hendrik G.; Arvidsson, Per I.; Naicker, Tricia; Govender, Thavendran (Synthesis, 2022)
A straightforward site-selective method for the direct carboxylation of resorcinols (3-hydroxyphenol derivatives), phenols, and indoles is reported. The products were obtained in moderate to high yields using supercritical carbon dioxide as an electrophile and solvent under basic conditions. This method offers solvent and metal free conditions without the cumbersome exclusion of air or water with convenient purification.
Keywords: supercritical carbon dioxide; Kolbe–Schmitt; C–H carboxylation; metal free; solvent free